2013
DOI: 10.1371/journal.pone.0069061
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Homologous Recombination and Non-Homologous End Joining Systems in Repairing Double-Strand Breaks during Cell Cycle Progression

Abstract: This study investigated the efficiency of Non-Homologous End Joining (NHEJ) and Homologous Recombination (HR) repair systems in rejoining DNA double-strand breaks (DSB) induced in CCD-34Lu cells by different γ-ray doses. The kinetics of DNA repair was assessed by analyzing the fluorescence decrease of γ-H2AX foci measured by SOID (Sum Of Integrated Density) parameter and counting foci number in the time-interval 0.5–24 hours after irradiation. Comparison of the two methods showed that the SOID parameter was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 43 publications
(50 reference statements)
4
57
0
1
Order By: Relevance
“…As cells in G 2 phase have twice the DNA and twice the number of DSBs as G 1 -phase cells (30)(31)(32)(33), we further examined ␥-H2AX foci in control and DDX1-depleted cells in G 1 versus G 2 phase. We used centromere protein F (CENP-F) immunostaining to distinguish cells in G 1 (when CENP-F is absent) from those in G 2 (when CENP-F expression peaks) ( Fig.…”
Section: Ddx1 Contributes To Dsb Repair and Cell Survival Post-irmentioning
confidence: 99%
See 3 more Smart Citations
“…As cells in G 2 phase have twice the DNA and twice the number of DSBs as G 1 -phase cells (30)(31)(32)(33), we further examined ␥-H2AX foci in control and DDX1-depleted cells in G 1 versus G 2 phase. We used centromere protein F (CENP-F) immunostaining to distinguish cells in G 1 (when CENP-F is absent) from those in G 2 (when CENP-F expression peaks) ( Fig.…”
Section: Ddx1 Contributes To Dsb Repair and Cell Survival Post-irmentioning
confidence: 99%
“…We used centromere protein F (CENP-F) immunostaining to distinguish cells in G 1 (when CENP-F is absent) from those in G 2 (when CENP-F expression peaks) ( Fig. 1E) (31,32,34). Compared to control cells, DDX1-depleted cells accumulated more ␥-H2AX foci in G 2 phase than in G 1 phase at 4 h after IR, with an ϳ60% increase in foci in G 2 compared to ϳ40% in G 1 (Fig.…”
Section: Ddx1 Contributes To Dsb Repair and Cell Survival Post-irmentioning
confidence: 99%
See 2 more Smart Citations
“…Once detected, DSBs can be repaired by 2 distinct mechanisms: HR, which acts preferentially in S and G2 phases of the cell cycle, and NHEJ, which is active throughout the whole cell cycle. 18,19 The formation of DSBs is always followed by the phosphorylation of the histone H2AX, a variant of the H2A protein family, which is a component of the histone octamer in nucleosomes. 20 Previous studies have shown that gH2AX can act as a highly sensitive and general marker of DNA damage induced by various ICL-inducing agents such as nitrogen mustards and platinumbased drugs.…”
Section: Introductionmentioning
confidence: 99%